2016
DOI: 10.1007/s10903-016-0490-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Suicide Behaviours in Immigrant and Ethno-Cultural Minority Groups: A Systematic Review

Abstract: This paper reviews recent literature on factors influencing suicide behaviours, including thoughts, plans, and attempts, in immigrant and ethno-cultural minority groups, to inform a more comprehensive understanding of suicide behaviours in increasingly culturally diverse populations. Thirty-three studies published between 2002 and 2013 were identified through digital databases searches and included in this review. Analysis of study findings focused on impacts of ethno-cultural identity and acculturation, other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 75 publications
2
33
0
1
Order By: Relevance
“…Acculturation issues were also shown to be associated with difficulties gaining employment, financial stress, social isolation and poor living conditions, all of which increased the risk of suicide among study participants. This finding is consistent with previous reviews which has found a relationship between acculturation stress and both depression and suicidal ideation in refugee and immigrant populations (Lai et al, 2017;Wyatt, Ung, Park, Kwon, Trinh-Shevrin, 2015).…”
Section: Acculturationsupporting
confidence: 93%
See 1 more Smart Citation
“…Acculturation issues were also shown to be associated with difficulties gaining employment, financial stress, social isolation and poor living conditions, all of which increased the risk of suicide among study participants. This finding is consistent with previous reviews which has found a relationship between acculturation stress and both depression and suicidal ideation in refugee and immigrant populations (Lai et al, 2017;Wyatt, Ung, Park, Kwon, Trinh-Shevrin, 2015).…”
Section: Acculturationsupporting
confidence: 93%
“…Research has found a relationship between immigration and higher rates of psychological distress and mental illness which is thought to be a key risk factor for suicide (Fazel, Wheeler, & Danesh, 2005). Other common risk factors for suicide in this population include difficulties with cultural assimilation and acculturation, social isolation, language barriers, and separation from family (Lai, Li, & Daoust, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Since this is an observational study, inference on causal relations is always limited and subject to confounding by unmeasured factors. Strong cultural pressures to avoid legal implications of homicide and the stigma associated with suicide homicides and suicides may be misclassified as unintentional firearm injury deaths [40], specially when intent is not clear. This fact can also impact the garbage code redistribution process of undetermined intention deaths, specially in states where SIM present lower quality of causes of death.…”
Section: Discussionmentioning
confidence: 99%
“…There are no available records for immigration status available for analysis in the current study. Future studies could incorporate this information, in view of reviews of recent research highlighting contribution of acculturation stress to suicide risk [ 12 , 49 , 57 ]. A lack of a control group also limits how the data could be interpreted.…”
Section: Discussionmentioning
confidence: 99%